Chemical genetics in Silene latifolia elucidate regulatory pathways involved in gynoecium development - Bačovský, Václav; Čegan, Radim; Tihlaříková, Eva; Neděla, Vilém; Hudzieczek, Vojtěch; Smrža, Lubomír; Janíček, Tomáš; Beneš, Vladimír; Hobza, Roman (Journal of experimental botany, 2022)
Dioecious plants possess diverse sex determination systems and unique mechanisms of reproductive organ development; however, little is known about how sex-linked genes shape the expression of regulatory cascades that lead to developmental differences between sexes. In Silene latifolia, a dioecious plant with stable dimorphism in floral traits, early experiments suggested that female-regulator genes act on the factors that determine the boundaries of the flower whorls. To identify these regulators, we sequenced the transcriptome of male flowers with fully developed gynoecia, induced by rapid demethylation in the parental generation. Eight candidates were found to have a positive role in gynoecium promotion, floral organ size, and whorl boundary, and affect the expression of class B MADS-box flower genes. To complement our transcriptome analysis, we closely examined the floral organs in their native state using field emission environmental scanning electron microscopy, and examined the differences between females and androhermaphrodites in their placenta and ovule organization. Our results reveal the regulatory pathways potentially involved in sex-specific flower development in the classical model of dioecy, S. latifolia. These pathways include previously hypothesized and unknown female-regulator genes that act on the factors that determine the flower boundaries, and a negative regulator of anther development, SUPERMAN-like (SlSUP).
Keywords: gynoecium; rostliny; Plants; Androhermaphrodite; flower development; HANABA TARANU (GATA18); fenotyp; Phenotype; sex chromosomes; Ovule; dioecy; květy; Flowers; SUPERMAN-like (SlSUP); Silene; vajíčko rostlin; Silene latifolia